Strategi Komunikasi Pemasaran pada Jasa Transportasi Teman Bus Mamminasata pada Media Sosial di Kota Makassar - Muhammad Afdal Zulfikar; Nurdyansa Nurdyansa; Erniwati Erniwati (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This study aims to determine the Marketing Communication Strategy for Teman Bus Mamminasata Transportation Services on Social Media in Makassar City. The method used is the Qualitative Method using data collection techniques through interviews and documentation, while the targets of this study are the transportation agency, passengers, and the community. The results of this study indicate that the application of Communication Strategy to Teman Bus Maminasata transportation services through social media has not been carried out systematically. It can be seen in several posts on Teman Bus Mamminasata social media accounts that were updated 2 years ago, although the marketing strategy carried out by the transportation agency is in the form of public socialization through forums, visits and events, but this does not affect public interest in using Teman Bus Mamminasata. Therefore, the application of marketing strategies through social media can help managers to easily disseminate information related to tutorials on using Teman Bus Maminasata, as well as the routes taken by this public transportation.